KONSTRUKSI IDENTITAS AGAMA DAN BUDAYA ETNIS MINANGKABAU DI DAERAH PERBATASAN: Perubahan Identitas dalam Interaksi Antaretnis di Rao Kabupaten Pasaman Sumatera Barat - Syafwan Rozi (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2013)
This dissertation discusses the rise of religious and ethnic identity change in a frontier area in West Sumatera. Its analysis focuses on inter-ethnic interaction between Minangkabau people and other ethnic groups in a frontier area of Rao, Pasaman. This study founds that social relationship in a frontier area took place in the form of individual relationships between the Minangkabau people with the Mandailing people. In their social interaction, these communities were engaged in the process of cultural contact, conflict or competition, accommodation, assimilation, adaptation, aculturation, negotiation and contestation. This study confirms that the process of interaction affects the religious and cultural identity change. Finally, the construction of religious and Minangkabau ethnic culture in a frontier area formed a new identity which was established from the synthesis of a long process of social interaction. The construction of religious and cultural identity formed a religious and ethnic conflict prevention model.Keywords: Construction of Identity, Religious and Ethnic Identity, Frontier Area.